Development of Flip Book-Based Economics Teaching Materials To Improve The Economic Learning Outcomes of Students In Class Xi Man 2 Deli Serdang In Academic Year 2021/2022 - Fitri Annisa Harahap; Saidun Hutasuhut; Thamrin Thamrin (Publikasi Indonesia, 2023)
The purpose of this study was to (1) determine the feasibility of flip book-based economics teaching materials in improving economic learning outcomes for class XI MAN 2 Deli Serdang students. (2) Knowing the effectiveness of flip book-based economics teaching materials in improving economic learning outcomes for class XI MAN 2 Deli Serdang students. This type of research is R & D research using the Borg and Gall development model. The subjects of this study consisted of two material experts, one learning media expert, one learning model expert, and 60 students of class XI MAN 2 Deli Serdang. As an object in this study, students' responses to learning media and student learning outcomes tests. The results showed (1) the expert test of learning materials was in the very good classification (94.44%), (2) the learning media expert test was in the very good classification (96.00%), (3) the expert test of the learning model was very good classification (95.18%). Based on the results of the learning tests, it is known that the average value of the control class is 67.69 and that of the experimental class is 85, and the two classes have a difference in value of 17.7. The results of the submission of the hypothesis prove that (1) Flipbook-Based Economics Teaching Materials to Improve Economic Learning Outcomes of Class XI MAN 2 Deli Serdang Academic Year 2021/2022 are appropriate for use (2) there is a significant difference between student learning outcomes using flipbook-based economics teaching materials with the learning outcomes of students who use textbooks. This is indicated by the results of data processing on the results of the post test obtained tcount = 10.691. At a significant level (? = 0.05) with dk 58 obtained ttable = 1.167 so that tcount > ttable. The average effectiveness of learning outcomes in the use of flipbook-based economics teaching materials is 85%, while the group of students who use textbooks is 68%. From this data it proves that the use of flip book-based economics teaching materials is more effective in increasing students' knowledge and competence in learning national income than without using flip book-based economics teaching materials